2019
DOI: 10.1002/adfm.201808152
|View full text |Cite
|
Sign up to set email alerts
|

Fully Solution‐Processed Photonic Structures from Inorganic/Organic Molecular Hybrid Materials and Commodity Polymers

Abstract: Managing the interference effects from multiple thin-layer structures allows for the control of optical transmittance and reflectance properties -often with very high precision. Widely used and technologically significant examples of such structures are antireflection coatings (ARCs) and distributed Bragg reflectors (DBRs), which rely on the careful control of destructive and constructive interference, respectively, between incident and reflected/transmitted radiation. While these structures have been known fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(57 citation statements)
references
References 28 publications
4
52
0
Order By: Relevance
“…In order to scrutinize 3D laser machining as a methodology toward complex photonic structures, we selected titanium oxide hydrates/PVAl hybrids as model material system for RI patterning because it has been shown that this hybrid material's RI can be readily tuned via its composition and heat exposure. Indeed, an increase of the RI of up to 1.83 at 550 nm, induced upon a thermal treatment (multistep annealing on hot plate at 150 °C), has been reported, [ 19 ] achieved for a material of 60 vol% inorganic content. For such a hybrid material, e.g., made from TiCl 4 , the change in refractive index was attributed to the thermal activation of further hydrolysis and condensation reactions of OH and Cl groups present in the pristine hybrid material.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to scrutinize 3D laser machining as a methodology toward complex photonic structures, we selected titanium oxide hydrates/PVAl hybrids as model material system for RI patterning because it has been shown that this hybrid material's RI can be readily tuned via its composition and heat exposure. Indeed, an increase of the RI of up to 1.83 at 550 nm, induced upon a thermal treatment (multistep annealing on hot plate at 150 °C), has been reported, [ 19 ] achieved for a material of 60 vol% inorganic content. For such a hybrid material, e.g., made from TiCl 4 , the change in refractive index was attributed to the thermal activation of further hydrolysis and condensation reactions of OH and Cl groups present in the pristine hybrid material.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the presence of the inorganic species still leads to an increase in RI while keeping the light transmission high (no light scattering occurs as no nanoparticles or aggregates form) and the chromatic dispersion low. [18,19] Such hybrids offer many opportunities for optical device engineering, and they may pave the way for the straightforward design and fabrication of high-performance 3D photonic circuits, provided a suitable index patterning procedure is identified. The reason is that the overall light management in photonic devices requires precise patterning of the refractive index, ideally in two or three dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Bragg modes do not require precise layer thicknesses which means low-quality, low-cost DBRs such as all-plastic ones can be used. 37,38 Importantly, the color temperature depends on the DBR while the internal quantum efficiency depends on the preconversion OLED. Naturally, changing the emitter to something other than TDAF can also affect the color temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Our device architecture does not depend on the substrate and incorporates metallic contacts instead of indium tin oxide films which are difficult to control and contain the scarce material indium. The Bragg modes do not require precise layer thicknesses which means low-quality, low-cost DBRs such as all-plastic ones can be used. , Importantly, the color temperature depends on the DBR while the internal quantum efficiency depends on the preconversion OLED. Naturally, changing the emitter to something other than TDAF can also affect the color temperature.…”
Section: Discussionmentioning
confidence: 99%